DETERMINANTS OF CUSTOMER LOYALTY: A LITERATURE REVIEW AND FUTURE DIRECTION - Nur Najwa binti Ies; Nazlyatul Nazlya binti Mat Salim; Nur Fazreen binti Mazlan; Anis Noraina binti Aminuddin; Syukurriah binti Idrus (International Journal of Accounting, Finance and Business, 2022)
The purpose of this paper was to analyse previous on customer loyalty fromdifference academic perspective. The customer loyalty was resulted from a good customerrelationship by a company which might develop long term relationship between customer andthe brand of the company. One of the reasons of strong attachment between customer towardsone brand were because of effective marketing strategies. This review of literature was fromfew search engine Scopus. Customer Loyalty was also a result when a business continuallymeets and exceeds the needs of its customers. It's all about like and trusting the product andbrand. This review paper tends to examine the concept of customer loyalty and its relevant inenhancing the customer relationship. The literature review on customer loyalty has beendetermine from 2016 -2022 using few databases search. The review discovered a number ofantecedents and their value in terms of consumer loyalty. It is hope that this review will providemore insight about customer loyalty and research priorities.